Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/foods12020373
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immune-Active Peptides in Casein Hydrolysates and Its Transport Mechanism on a Caco-2 Monolayer

Abstract: In this study, we investigated the transport mechanism of immune-active peptide fragments isolated from casein gastrointestinal hydrolysates via a Caco-2 monolayer. The casein gastrointestinal hydrolysates could stimulate B-lymphocyte proliferation and reduce the TNF-α level. Then, we identified the bioactive peptide fragments derived from casein gastrointestinal hydrolysis using LC-MS/MS. Our results demonstrated that the transport mechanism of five immune-active peptides at the cell level was bypass transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Similarly, lactoferrin (LF) and casenoglycopeptides (CGP) derived from K‐casein have been proven to improve lymphocyte function. In vitro experiments have shown that peptides generated from the enzymatic cleavage of α and β‐casein can also improve human lymphocyte activity (Ha et al, 2021 ; Marcone et al, 2017 ; Xue et al, 2023 ).…”
Section: Animal‐sourced Foodsmentioning
confidence: 99%
“…Similarly, lactoferrin (LF) and casenoglycopeptides (CGP) derived from K‐casein have been proven to improve lymphocyte function. In vitro experiments have shown that peptides generated from the enzymatic cleavage of α and β‐casein can also improve human lymphocyte activity (Ha et al, 2021 ; Marcone et al, 2017 ; Xue et al, 2023 ).…”
Section: Animal‐sourced Foodsmentioning
confidence: 99%